Human governance: how ethical behaviour of accountants can be improved? - Muhamad, Haslinah; Salleh, Arfah; Abu Kasim, Nor Aziah; Suppiah, Susela Devi K. (Human Resource Management Academic Research Society, 2019)
This article reports the development of philosophy underpinning ethics education especially in the accounting field from the oldest systematic philosophers in western culture as a starting point to the current situation of teaching ethics and the suggestion of new direction by the installation of the concept of human governance. Compare to the oldest era, education in the era of industrial revolution emphasises on the development of technical skills and producing specialists and scientists. Postmodernism scholars find that schools in this era are not teaching humanities in ways conducive to cognitive development or respect for traditional knowledge and values. Consequently, critiques on this kind of education started emphasis in the late eighties and nineties. However, only after the Enron scandal, attention is given to develop long-term strategy to tackle the issue of unethical behaviour among accountants through stringent rules and regulation, code of ethics, ethics education and research. The need to adopt a new philosophy as a supplement in teaching ethics has arisen. This paper proposed to introduce the concept of human governance into accounting ethics education especially at university level. Additionally, this paper had also provided the overview of the concept of human governance.